2017
DOI: 10.3127/ajis.v21i0.1378
|View full text |Cite
|
Sign up to set email alerts
|

Exploring mHealth Participation for Emergency Response Communities

Abstract: We explore the challenges of participation by members of emergency response communities who share a similar condition and treatment, and are called upon to participate in emergency events experienced by fellow members. Smartphones and location-based social networking technologies present an opportunity to re-engineer certain aspects of emergency medical response. Life-saving prescription medication extended in an emergency by one individual to another occurs on a micro level, anecdotally documented. We illustr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…UnityPhilly is an Emergency Response Community (ERC) app designed to support laypersons in signaling and responding to opioid overdose incidents [ 24 , 25 ]. The app SOS function enabled volunteers to signal an overdose incident with a single button press, initiating an automated alert to other nearby volunteer app users ( Fig.…”
Section: Methodsmentioning
confidence: 99%
“…UnityPhilly is an Emergency Response Community (ERC) app designed to support laypersons in signaling and responding to opioid overdose incidents [ 24 , 25 ]. The app SOS function enabled volunteers to signal an overdose incident with a single button press, initiating an automated alert to other nearby volunteer app users ( Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Research suggests that nearby patient-peers who maintain long-term EAI prescriptions can potentially deliver their personal EAI to the patient in need through a proximity-based emergency response communities (ERC) app [8,9]. As described in Figure 1, ERC apps dispatch nearby registered patients with allergy to help a patient in immediate need of an EAI, in certain configurations following the approval of EMS.…”
Section: Introductionmentioning
confidence: 99%
“…The state of telehealth improving overall treatment outcomes (Khodadad-Saryazdi, 2021). Prior research has shown that IoT has application areas that benefit patients, communities, physicians, healthcare facilities and insurance providers (Hsiao et al, 2019;Khalemsky and Schwartz, 2017;Pan et al, 2019;Schwartz et al, 2017;Sneha and Varshney, 2009). Wearable technologies such as fitness trackers and other wirelessly linked devices such as cardiovascular monitoring devices and glucometers enable patients to get customized treatment (Aboelmaged et al, 2021;Vesselkov et al, 2018).…”
Section: Science Mappingmentioning
confidence: 99%
“…These gadgets can be programed to remind users of calorie counts, activity checks, medical appointments and blood pressure changes, among others (Ben Arfi et al, 2021;Pan et al, 2019). Furthermore, IoT has transformed the lives of many people, particularly elderly patients and patients who live alone, by allowing continuous monitoring of their medical conditions (Almobaideen et al, 2017;Eze et al, 2019;Meng et al, 2020;Schwartz et al, 2017). For example, IoT-based sensing mechanism automatically notifies family members and physicians when a person's normal health condition is disturbed, thereby alerting them of potential health complications (Almobaideen et al, 2017;Go Jefferies et al, 2019;Khalemsky and Schwartz, 2017).…”
Section: Science Mappingmentioning
confidence: 99%